A combination of genome-wide and transcriptome-wide association studies reveals genetic elements leading to male sterility during high temperature stress in cotton - Ma, Yizan (The New phytologist, 2021)
© 2021 The Authors New Phytologist © 2021 New Phytologist Foundation.